Answer:
Step-by-step
Let the given number be n>2.
For n even, n2+((n/2)2–1)2=((n/2)2+1)2.
For n odd, n2+((n2–1)/2)2=((n2+1)/2)2
use the forumla to find u r answer
standard form of a pythagorean triplet is 2m, m²+1, m²-1
let us take 2m as 36. so
2m=36, m=36/2
therefore m=18
m²+1 =18²+1 = 324+1 =325
m²-1 =18²-1 = 324-1 =323
therefore 36,325,323 form a pythagorean triplet.
For checking, 36²+323² should be equal to 325²
Tell me if this was helpful....
Describe the graph of y+3x^2 and compare it with the graph of y=x^2
Answer:
y = 3x^2 is compressed by 3.
As y = x^2 is the parent graph, you can see how big a difference 3 makes.
Hope this helps!
(Red: y = 3x^2)
(Blue: y = x^2)
The transformation for the given function is vertical compression or stretch.
The given functions are y=3x² and y=x².
What is the function?Functions are the fundamental part of the calculus in mathematics. The functions are the special types of relations. A function in math is visualized as a rule, which gives a unique output for every input x.
The graph for the given functions can be determined as follows
To find the transformation, compare the expression to the parent function and check to see if there is a horizontal or vertical shift, reflection about the x-axis or y-axis, and if there is a vertical stretch.
Horizontal Shift: None
Vertical Shift: None
Reflection about the x-axis: None
Reflection about the y-axis: None
Vertical Compression or Stretch: Compressed
Therefore, the transformation for the given function is vertical compression or stretch.
To learn more about the function visit:
https://brainly.com/question/28303908.
#SPJ5
2 Points
Choose the number below that represents the digit in the tens place of the
number 184
A. 8
B. 4
C. 1
D. 10
Which of the trigonometric expressions represent an inverse function?
Answer:
the second one:
tan-1(xdegree)
Step-by-step explanation:
3) $1,470 at 5% compounded
semiannually for 4 years
Answer:
29400
Step-by-step explanation:
Im pretty sure
The math question is attached below.
FOR 13+POINTS
Answer:
91.7
Step-by-step explanation:
V = π x r² x h
V = π x 2² x (8-0.7)
V = π x 4 x 7.3
V = 91.73
3.) Calculate the volume of the rectangular prism shown.
Answer:
162
Step-by-step explanation:
V = LWH
L = 3
W = 6
H = 9
3 * 6 * 9 = 162
Simplify 7(x + 3). xxxxxxxxxxx
Answer:
[tex]7x+21[/tex]
Step-by-step explanation:
[tex]7(x + 3)[/tex]
[tex]7(x)+7(3)[/tex]
[tex]7x+21[/tex]
Answer:
7x + 21
Step-by-step explanation:
7 x X=7X
7 x 3=21
When the equation 2x+15−−−−−−√−x=0 is solved correctly, the solutions are x=−3 and x=5.
Which, if any, of the solutions are not valid?
A) The solution x=−3 is not valid.
B) The solution x=5 is not valid.
C) Neither solution is valid.
D) Both solutions are valid.
Hi can I please get some help please thank you please please I need it WILL MARK AS BRAINLIEST !!!
Answer: D
Step-by-step explanation:
A and C are linear equations therefore we can eliminate them.
We are left betwen C and D.
C.
x²=25
x=5, x=-5
For C, we can eliminate because when you solve for x, you get 2 linear equations. You may see the x² and think it's linear, but when you solve it, you get 2 linear equations.
We are left with D. Even if you graph it and it doesn't look like a parabola or quadratic, it is still a quadratic equaiton. The 1/ makes it split both ways.
What is the probability a King is chosen? Express your answer as a fraction, in simplest form.
A(1/52
B(1/13
C(1/4
D(4/13
Answer:
1/13
Step-by-step explanation:
In a deck of 52 cards, there are 4 kings
P(king) = number of kings / total cards
P (king) = 4/52
= 1/13
What is the solution to this equation?
3(4x+6) = 9x + 12
O A. x= -2
B. X=-10
O c. x= 2
O D. x= 10
Answer:
I think it's A) x= - 2
Hope this helps..
The solution of the equation is,
⇒ x = - 2
What is an expression?Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The equation is,
⇒ 3 (4x + 6) = 9x + 12
Now,
Solve the equation as;
⇒ 3 (4x + 6) = 9x + 12
⇒ 12x + 18 = 9x + 12
⇒ 12x - 9x = 12 - 18
⇒ 3x = - 6
⇒ x = - 6/3
⇒ x = - 2
Learn more about the mathematical expression visit:
brainly.com/question/1859113
#SPJ2
For 20 points
Please Help it is due today and I I don't get how to find the height. I am a 7th grader and it is a 6th grade work for the whole class. I didn't even do this in 6th grade it is hard
Please Help
Answer:
The height of trapezoid is 7km.
Step-by-step explanation:
Given that the area of trapezoid formula is A = 1/2×(a+b)×h where a and b represents the length and h is the height. By substituing the values, you are able to find the height :
[tex]area = \frac{1}{2} \times (a + b) \times h[/tex]
Let a = 4km,
Let b = 8km,
Let area = 42km²,
[tex]42 = \frac{1}{2} \times (4 + 8) \times h[/tex]
[tex]42 = \frac{1}{2} \times 12 \times h[/tex]
[tex]42 = 6 \times h[/tex]
[tex]6h = 42[/tex]
[tex]h = 7 \: km[/tex]
Answer: 7km
Step-by-step explanation:
the math question is attached below
and please explain how you got the answer
Answer:
[tex]20\pi units^3[/tex]
Step-by-step explanation:
Answer:
V = 62.8 units³
Step-by-step explanation:
Once the area of a circle is:
[tex]A=\pi r^2[/tex]
The volume of a cylinder is:
[tex]V=\pi r^2 h[/tex]
where [tex]h[/tex] is the height of the cylinder.
Once, [tex]r=2 \text{ and } h=5[/tex]
[tex]V=3.14 \cdot 2^2 \cdot 5\\V=3.14 \cdot 20\\V=62.8 \text{ units cubed}[/tex]
Which expression is equivalent to the given expression?
(12g^2h^7)(3g^-2h^-4)
Answer:
B
Step-by-step explanation:
(12g²h⁷)(3g⁻²h⁻⁴) = 12 * 3 * g²⁺⁽⁻²⁾ * h⁷⁺⁽⁻⁴⁾
= 36 * g⁰ * h³
= 36 * 1 * h³
= 36h³
Any variable or constant to the power of zero is 1
a⁰ = 1 ; 12⁰ = 1 ; (-5)⁰ = 1
Any one know this pls explain how u figured it out
Answer:
x=236
Step-by-step explanation:
44+80+x=360
x=solve it
The ordered pair below is a solution to which equation?
(40,5)
Answer: A
Step-by-step explanation:
Solve the following equation by using the multiplicative inverse. MUST SHOW WORK
5/6x = - 10
Answer:
5/6x = -10
=> 5/6x = -10/1
by cross multiplication
=> 6x × - 10 = 5 × 1
=> 6x = 5 × 1 / -10
=> 6x = 1/-2
=> x = 1/-2 ×6
=> x = 1/-12
Lucia surveyed the students in her class and made a dot plot of the results. What question could Lucia have asked?
Answer:
How many days do you exercise in a week?
Step-by-step explanation:
The topic is students' weekly exercise so the question has to be about that. also, there are up to 7 days worth of data and there a 7 days in a week. so she most likely asked the question, "How many days do you exercise in a week?".
Please help me answer this question.
Answer: 5 miles
Step-by-step explanation:
Slope of the line that passes through (2,1) and (8,4), please!
Answer:
Slope is 1/2
Step-by-step explanation:
Slope Formula: [tex]\frac{y_{1}-y_{2}}{x_{1}-x_{2}} \\[/tex]
Plug in points: [tex]\frac{4-1}{8-2} =\frac{3}{6}=\frac{1}{2}[/tex]
URGENT!!!! What is the value of x in the equation 1.5(x + 4) – 3 = 4.5(x - 2)?
Answer:
[tex]x=4[/tex]
Step-by-step explanation:
[tex]1.5(x + 4) - 3 = 4.5(x - 2)[/tex]
[tex]1.5x+6-3=4.5x-9[/tex]
[tex]1.5x+3=4.5x-9[/tex]
[tex]3+9=4.5x-1.5x[/tex]
[tex]12=3x[/tex]
[tex]x=4[/tex]
Answer:
[tex]x = 4[/tex]
Step-by-step explanation:
[tex]1.5(x + 4) - 3 = 4.5(x - 2) \\ 1.5x + 6 - 3 =4.5x - 9 \\ 6 - 3 + 9 = 4.5x - 1.5x \\ 12 = 3x \\ \frac{12}{3} = \frac{3x}{3} \\ x = 4[/tex]
hope this helps
brainliest appreciated
good luck! have a nice day!
WILL GIVE BRAINLIEST
Answer:
10/3
Step-by-step explanation:
6 length is 2 height.
So 10(6+4) length is 10/3 height
Answer:
x = 10/3
Step-by-step explanation:
These two triangles are similar by AA similarity, as they share angle A, and both have right angles.
Not we can set up a ratio:
6/(6+4) = 2/x
6/10 = 2/x
3/5 = 2/x
Multiply both sides by 5x,
3x = 10
Divide both sides by 3:
x = 10/3
12
Find the area of the shaded reagion.
5 in
\frac{(2_1-4_{2}) ^{4} } {2}
I will give you brainliest
Answer:
I think the answer is 8
Step-by-step explanation:
Simplify the following expression:
2x − 2y + 5z − 2x − y + 3z
x − 3y + 8z
2x − 2y + 8z
3y + 8z
−3y + 8z
Answer:
-3y+8z
Step-by-step explanation:
Here we want to combine all the like terms together to simplify the expression:
2x-2y+5z-2x-y+3z=\\ 2x-2x-2y-y+5z+3z=\\ -3y+8z
Answer:
a
Step-by-step explanation:
Zeke goes to a skate shop with his friend Tristan. Tristan buys a helmet that costs $28.75. Zeke finds a helmet that is [tex]\frac{3}{5}[/tex] of the cost of Tristan's helmet. If Zeke gives the cashier a $20 bill, how much change will he receive.
Answer: $2.75
Step-by-step explanation:
Zeke's helmet cost 3/5 x 28.75 = 17.25
Change = 20 - 17.25 = 2.75
Answer:
2.75
Step-by-step explanation:
Add the polynomials.
(x2−11x+6)+(x2+5)
Answer:
[tex] \boxed{2 {x}^{2} - 11x + 11} [/tex]
Step-by-step explanation:
[tex] = > ( {x}^{2} - 11x + 6) + ( {x}^{2} + 5) \\ \\ = > {x}^{2} - 11x + 6 + {x}^{2} + 5 \\ \\ = > {x}^{2} + {x}^{2} - 11x + 6 + 5 \\ \\ = > 2 {x}^{2} - 11x + 11[/tex]
Answer:
2x^2 - 11x +11
Step-by-step explanation:
combine like terms
Classify the real number.
-8
[mark all correct answers]
nts
a. Rational
b. Integers
c. Whole
d. Natural
e. Irrational
72
Answer:
a,c
Step-by-step explanation:
PLZZ HURRY
q1)
Simplify. 6(5p^3 − 6p)
Answer:
30p^3−36p
Step-by-step explanation:
6(5p^3−6p)
=(6)(5p^3+−6p)
=(6)(5p^3)+(6)(−6p)
=30p3−36p
Answer:
30p^3−36pStep-by-step explanation:
6(5p^3−6p)
(6)(5p^3+−6p)
(6)(5p^3)+(6)(−6p)
=30p^3−36p
This is not copied i did the work!
Please help! 19 points! Brainliest to best answer! Solve for the following equation step by step and justify your steps when using an exponential property. [tex]7x^4=\frac{7^2*7^3}{7^3^x}[/tex]
Answer:
ummm i dont know but try 16 35/21
Step-by-step explanation:
Answer: x^4 /7^3x-6
Step-by-step explanation:
7x^4 * 7^5 / 7^3x
7x^4 * 1 / 7^3x-5
Reduce expression with 7
x^4 * 1 / 7^3x-6
= x^4 / 7^3x-6